Application of the Think Aloud and System Usability Scale (SUS) Methods in Usability Evaluation in Online Transportation Applications for the Elderly - Aneke Putri Nadila; Tranggono; Mega Cattleya Prameswari Anissa Islami (Journal of Applied Informatics and Computing)
Technological advancements have driven the adoption of online transportation applications by various user groups, including the elderly. However, limitations in cognitive aspects and digital experiences cause barriers to application use. This study was conducted to evaluate the usability of online transportation applications for elderly users using the Think Aloud and System Usability Scale (SUS) methods. The evaluation was carried out through a series of tests with eight elderly respondents to measure effectiveness, efficiency, and user satisfaction. The Think Aloud method was used to explore the experiences and difficulties faced by the elderly on the application interface, respondents verbally expressed their thoughts and feelings during the testing process. The Think Aloud testing process is analyzed to identify the specification of the requirements that form the basis for the redesign of the application. The measurement results showed that the average application effectiveness value increased from 85% in the initial design to 100%. Efficiency values show a significant improvement from the initial design of 73% to 100% in the proposed improvement design. The average SUS score before the improvement was 61.25 in the marginal category, and increased to 81.25 in the acceptable category after the improvement design. The results of this study confirm that optimizing design based on the needs of the elderly can improve the user experience and accessibility of online transportation services.